Bit allocation approach of spatial modulation for multi-user scenario. (1st February 2019) - Siregar, Rahmat Faddli; Murti, Fahri Wisnu; Shin, Soo Young
Abstract: In this study, a multi-user bit allocation approach using spatial modulation (SM) technique is proposed. Massive connectivity can be covered using the proposed scheme such as for massive downlink (DL) internet of things (IoT). In the proposed scheme, like single-user DL SM, a single antenna is activated to send information to multiple DL users. At each user, the antenna index and constellation symbol are then estimated and converted into information bits. The information bits are extracted to obtain bits that are addressed only to the particular user. Consequently, both inter-channel and inter-user interference can be avoided among the users in the proposed scheme. As performance measures, average bit error probability (ABEP) and throughput are evaluated. It is shown that the ABEP of each user in the proposed scheme outperforms that in a single-user DL SM system by both analysis and simulation. The throughput analysis also shows that overall throughput of proposed system outperforms that in a single-user DL system. Moreover, the receiver complexity comparison between the existing technique with the proposed scheme for multi-user is presented. It is shown that the proposed system achieves the lowest receiver complexity compared to the others with the same system configurations. Finally, the energy efficiency comparison with the existing technique is also presented. It shown that the proposed system achieves lower energy consumption compared with the existing technique.